Do government agricultural policies affect production and export of cocoa in Ghana?. Issue 6 (19th September 2022) - Yusif, Hadrat; Ntreh, Emmanuel Nii Oseku; Sakyi, Daniel; Baidoo, Samuel Tawiah
Abstract : The contributions of the agricultural sector to economic growth of developing countries of which Ghana is no exception cannot be overemphasized. Despite the sector being the mainstay of the Ghanaian economy, it is still confronted with several challenges. As a result, several agricultural policies such as, cocoa sector strategy, cocoa disease and pest control and cocoa high technology programmes have been implemented over the years. This study therefore examines the impact of these policies on cocoa production as well as on export. Using annual time series data over the period 1961–2017, the interrupted time series analysis is employed to address the objective of the study. The results reveal that cocoa sector strategy, cocoa disease and pest control, and cocoa high technology have boosted cocoa production. With regard to the export of cocoa, it is revealed that only the cocoa sector strategy policy has promoted cocoa export. The policy implication of the results is that there is a need for the sustainability of these agricultural policies. In terms of contribution and novelty, this paper investigates the impact of all three agricultural policies [cocoa sector strategy (CSS), cocoa disease and pest control programme (CODAPEC) and cocoa high technology programme (CHTP)] that Ghana has implemented over the years regarding cocoa production, which previous studies have not considered. This paper is also the first study to examine the impact of these agricultural policies on export of cocoa in Ghana.